Storytelling as A Learning Tool in Architecture Design Studio: السرد القصصي كأداة تعليمية في استوديو التصميم المعماري - Danah Munir Tuffaha, Mehmet Harun Batirbaygil (Journal of engineering sciences and information technology, 2020)
This research examines the effect of applying Storytelling as a learning tool in architecture design studios classes. It aims to help overcome some of the current learning challenges and shortcomings in students’ design skills learning. Newly graduated students from schools of architecture are encountered with challenges surrounding their design skill capability when entering the professional practice. The researcher believes that these difficulties start in design studio classes. The gap between academic learning and practicing profession is a concern many scholars are continuously trying to tackle. The researcher investigates the shortcomings in design studio learning and suggests that Storytelling can be a learning tool to help students and teachers overcome these shortcomings. The researcher conducted a two-phase experiment in a design studio class at Okan University. In the first phase the Researcher collected data using quantitative and qualitative methods that illustrate the current condition of students’ design skills, as well as areas of shortcomings and challenges that need to be addressed. In the second phase, the Researcher used action research methodology and applied Storytelling as a strategy of combining reflective and experiential learning theories in design studio class. According to the outcomes at the final jury and collected questionnaires, the results of this experiment were generally successful. Most of the students proved significant progress in terms of design skills and creativity. Moreover, students’ presentation skills showed broad improvement and in return their self-confidence and understanding of submissions have advanced drastically. The researcher recommends this research to work as a model study for other scholars to adopt, develop and lead more similar researches in the future in other universities and design schools. The researcher also recommends this research be applied to earlier design studio classes.